Exploring Python Programming: A Project Based Learning-Centric Learning Experience - Karnando, Joni; Muskhir, Mukhlidi; Luthfi, Afdal (Universitas Pendidikan Ganesha, 2024)
Information technology has experienced significant developments in science and technology, including programming languages. One of the most popular programming languages today is Python. However, many students still have difficulty learning the Python programming language. These difficulties are caused by the lack of learning media that focus on the Python language, module explanations that are difficult to understand, and a lack of understanding of the library in the Python language. This research aims to create a Python programming language learning module focusing on the project-based Learning (PjBL) approach. The methodology used in this research is Research and Development (R&D). The data needed in this study were collected through questionnaires and learning outcomes exams with a subject of 28 students. The data in the effectiveness aspect is using the T-Test Test. This research results in a valid, practical, and effective PjBL-based Python programming language learning module. This module is considered valid by experts in media aspects with a value of 0.85 and material aspects with a value of 0.89. The practicality of this module is proven through positive responses from lecturers of 88.75%, student responses in the limited test of 88.5%, and the usage trial of 86.96%. Meanwhile, the effectiveness of this module can be seen from the classical completion rate of 82% and the gain score of 57%, and the t-test shows that this module significantly increases student learning outcomes in the Python programming language.